Performance Analysis of the State Civil Apparatus in the Housing and Settlement Area Services of Maluku Province - Alan Julian Putra Komala Alyona; Petronela Sahetapy; Hendrik Selanno; Dortje L. J. Lopulalan (Formosa Journal of Social Sciences (FJSS), 2024)
The phenomenon of lack of employee work discipline, work targets sometimes do not meet standards which occurs because there are delays in completion, minimal communication and cooperation between co-workers hinders work progress. The purpose of this paper is to analyze the performance of state civil servants at the Housing and Settlement Service of Maluku Province. Performance theory is the basis for analyzing this problem through sub-indicators of ability, motivation, knowledge and leadership using qualitative methods to produce a study of a more comprehensive phenomenon on the subject of research. The results of the study show: 1. The aspect of ability in achieving work targets that have been set based on SOPs is not running optimally because various obstacles are encountered, such as being slow in implementing reports and not being in accordance with the targeted time. 2. The motivation aspect needs to be improved because it influences the completion of work or tasks and responsibilities given to each employee